ANALISIS BREAK EVEN POINT (BEP) SEBAGAI ALAT PERENCANAAN LABA JANGKA PENDEK PADA UMKM KCHARIS JAYA PALEMBANG - Feni Repsi Melaresani, Feni Repsi Melaresani; Yulina, Bainil; AR, Sopiyan (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
This final report aims to analyse the application of the Break Even Point (BEP) method as a short-term profit planning at UMKM Kcharis Jaya Palembang. The main problem of this MSME is that there is no detailed classification of fixed costs and variable costs and no break even point analysis has been carried out as a basis for making useful decisions on sales and profit planning, especially short-term profits. The data collection methods of this final report are observation, interviews, documents and triangulation. The analysis focused on the classification of fixed costs, variable costs and sales to calculate BEP, Margin of Safety (MoS), and profit targets for 2022, 2023 and 2024. The results show that the application of BEP helps MSMEs to improve cost efficiency, knowing the minimum sales limit to avoid losses. The Margin of Safety (MoS) calculation shows the level of sales security, develops the right sales strategy and strengthens the basis for decision making in obtaining optimal short-term profits. Meanwhile, the profit target provides a reference for the sales volume to achieve the expected profit. Keywords: Break Even Point, Margin of Safety, Profit Target, Short Term Profit Planning